Avian Influenza: Trade Issues - Moore, Toby; Morgan, Nancy (Council for Agricultural Science and Technology (CAST), 2006)
Although much of the concern about a possible pandemic outbreak of highly pathogenic avian influenza revolves around human health outcomes, the potential repercussions on trade issues will also be significant. The United States is a major exporter of poultry products amounting to approximately 2 billion worth of broilers, turkeys, and eggs annually. International reporting of an avian influenza outbreak could have the effect of virtually stopping this trade–and that in other countries as well–overnight.